Detection of recombinant EPO in blood and urine samples with EPO WGA MAIIA, IEF and SAR‐PAGE after microdose injections. Issue 11 (4th November 2013) - Dehnes, Yvette; Shalina, Alexandra; Myrvold, Linda
Abstract : The misuse of microdoses of performance enhancing drugs like erythropoietin (EPO) constitutes a major challenge in doping analysis. When injected intravenously, the half‐life of recombinant human EPO (rhEPO) like epoetin alfa, beta, and zeta is only a few hours and hence, the window for direct detection of rhEPO in urine is small. In order to investigate the detection window for rhEPO directly in blood and urine with a combined affinity chromatography and lateral flow immunoassay (EPO WGA MAIIA), we recruited nine healthy people who each received six intravenously injected microdoses (7.5 IU/kg) of NeoRecormon (epoetin beta) over a period of three weeks. Blood and urine samples were collected in the days following the injections and analyzed with EPO WGA MAIIA as well as the current validated methods for rhEPO; isoelectric focusing (IEF) and sarcosyl polyacrylamide gel electrophoresis (SAR‐PAGE). For samples collected 18 h after a microdose, the sensitivity of the EPO WGA MAIIA assay was 100% in plasma and 87.5% in urine samples at the respective 98% specificity threshold levels. In comparison, the sensitivity in plasma and urine was 75% and 100%, respectively, with IEF, and 87.5% in plasma and 100% in urine when analyzed with SAR‐PAGE. We conclude that EPO WGA MAIIA is a sensitive assay for the detection of rhEPO, with the potential of being a fast, supplemental screening assay for use in doping analysis. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : 18 h post‐injection, EPO WGA MAIIA could detect a dose of 7.5 IU/kg of rhEPO in blood and urine with 100% and 87.5% sensitivity, respectively. The results were confirmed with 100% specificity in urine and 87.5 % specificity in blood with SAR‐PAGE. EPO WGA MAIIA has the potential to be a fast and sensitive supplemental screening assay for rhEPO in doping analysis.